BENTUK PENYIMPANGAN SOSIAL DALAM NOVEL PINTU TERLARANG KARYA SEKAR AYU ASMARA - Ochio, Filtri; Zulfitriyani; Putri, Febrina Riska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by various forms of social deviance committed by thecharacters in the novel Pintu Terlarang by Sekar Ayu Asmara. The purpose of thisresearch is to describe the forms of social deviance in the novel Pintu Terlarang bySekar Ayu Asmara. This research is a qualitative study. The method used in thisresearch is descriptive analysis. The results of this research show various forms ofsocial deviance committed by the characters in the novel Pintu Terlarang by SekarAyu Asmara. The forms of social deviance found in the novel Pintu Terlarang bySekar Ayu Asmara are divided into three, namely criminal acts, sexual deviance,and lifestyle deviance